New product development : managing and forecasting for strategic success - Thomas, Robert J. (New York : J. Wiley, 1993)
Dr. Thomas shows how to take control of the new product development process by effectively forecasting market opportunities, estimating sales and profits, designing marketing efforts, timing the launch of new products, and tracking products after launch. He shows that managing and forecasting successful new product developments are an interactive process involving all members of the new product team
Includes bibliographical references (p. 319-338) and indexes.
Keywords: Product management; New products Development; Marketing